LASSO-driven inference in time and space - Victor Chernozhukov; Wolfgang Härdle; Chen Huang; Weining Wang (Centre for Microdata Methods and Practice (cemmap), 2018)
We consider the estimation and inference in a system of high-dimensional regression equations allowing for temporal and cross-sectional dependency in covariates and error processes, covering rather general forms of weak dependence. A sequence of large-scale regressions with LASSO is applied to reduce the dimensionality, and an overall penalty level is carefully chosen by a block multiplier bootstrap procedure to account for multiplicity of the equations and dependencies in the data. Correspondingly, oracle properties with a jointly selected tuning parameter are derived. We further provide high-quality de-biased simultaneous inference on the many target parameters of the system. We provide bootstrap consistency results of the test procedure, which are based on a general Bahadur representation for the Z-estimators with dependent data. Simulations demonstrate good performance of the proposed inference procedure. Finally, we apply the method to quantify spillover effects of textual sentiment indices in a financial market and to test the connectedness among sectors.
Keywords: C12; C22; C51; C53; 330; LASSO; time series; simultaneous inference; system of equations; Z-estimation; Bahadur representation; martingale decomposition